Pengembangan Laboratorium Virtual dan Animasi 3 Dimensi (Le Chatelier Virtual Laboratory) Pada Materi Kesetimbangan Kimia - Mardhiya, Julia; Laila, Fadhilah Nur (Oxygenius: Journal Of Chemistry Education, 2024)
The digital era requires teachers and prospective teachers to innovate in the development of effective, efficient and not boring learning media. This study aims to develop interactive learning media based on virtual laboratories and 3-dimensional animation on chemical equilibrium material called Le Chatelier Virtual Laboratory. The research and development method used is 4D. The research study was used to determine the feasibility and student responses to virtual laboratory-based interactive learning media and 3D animation on chemical equilibrium. Product validation results were performed by experts using Aiken's V data analysis. The validity result reached a value of 0.91, a category with high validity. The small-scale trial produced a fairly good response with an overall quality percentage of 83.46%. This study concluded that learning media can be used in the learning process and further research can be carried out at the disseminate stage (large scale implementation).